2018
DOI: 10.1515/chem-2018-0104
|View full text |Cite
|
Sign up to set email alerts
|

The biological activities of Arabis alpina L. subsp. brevifolia (DC.) Cullen against food pathogens

Abstract: In this study, in vitro biological activities of both methanol and ethanol extracts of Arabis alpina subsp. brevifolia were investigated. Also, the phenolic components of this plant was examined in this study. The extracts were tested against the eight strains of food pathogens for their antimicrobial activities by utilizing minimum inhibitory concentration (MIC) and disc diffusion assay. The non-enzymatic antioxidant activities were determined according to scavenging of the free radical 2,2-diphenyl-1-picrylh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Contemporary food market trends, associated with consumer expectations, are directed at natural products of high quality, low processing and long shelf-life [4,5]. The current fashion for healthy nutrition and care for the natural environment make it necessary to replace chemical preservatives with naturally-formed ones [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary food market trends, associated with consumer expectations, are directed at natural products of high quality, low processing and long shelf-life [4,5]. The current fashion for healthy nutrition and care for the natural environment make it necessary to replace chemical preservatives with naturally-formed ones [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Balpinar reported that methanol and ethanol extracts of A. alpina L. subsp. brevifolia exhibited antimicrobial activity against S. typhimurium (Balpinar, 2018). In that study extracts had no activity against Bacillus subtilis, Staphylococcus aureus, Salmonella Typhimurium, Enterococcus faecalis, Escherichia coli, Listeria monocytogenes, and the fungus Candida albicans.…”
mentioning
confidence: 77%
“…There are many species in the Brassicaceae family that are used in traditional medicine and foods these are also recognized as the functional food. Brassicaceae family has received a great deal of attention in recent years because of its antioxidative and antimicrobial properties (Balpinar, 2018). The main metabolite of Brassicaceae is glucosinolates that contain sulfur.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations